RECRUITMENT PROCESS FOR EMPLOYEES WITH GRADE DISABILITIES 4 (CREW OF STORE): PROSES REKRUTMEN KARYAWAN PENYANDANG DISABILITAS GRADE 4 (CREW OF STORE) - Khaeruman Khaeruman (Indonesian Journal of Economy, Business, Entrepreneurship and Finance, 2021)
Recruitment is a series of processes to search for prospective workers who have interests and potential that match the position that the company is needing. Disability is a new term to describe the condition of someone who has disabilities in the form of physical, mental, cognitive, sensory, emotional, developmental or a combination of these conditions. This research was conducted using qualitative methods, both with field research and interviews with related parties, in combination with literature studies, whether books, journals, or other sources. The recruitment system for prospective employees, acceptance of Grade 4 (crew of store/cashier) employees by the HRD Division based on requests and plans from vendor companies regarding the needs of human resources, to fulfill these requests. The results of the research and discussion done by the authors above can be concluded during the research at PT. Sumber Alfaria Trijaya, especially in the Human Resource section, is a recruitment activity for every company, which is the most important thing, because to get quality Human Resources must go through a selection stage